Kinetics analysis and automated online screening of aminocarbonylation of aryl halides in flow. Issue 3 (22nd February 2016) - Moore, Jason S.; Smith, Christopher D.; Jensen, Klavs F.
Abstract : The Pd-catalyzed aminocarbonylation of aromatic bromides was investigated in both a silicon microreactor and a packed-bed tubular reactor. An automated transient temperature ramp method with in-line IR analysis led to significantly more rapid determination of reaction kinetics than traditional steady-state screening for offline GC analysis. Abstract : Temperature, pressure, gas stoichiometry, and residence time were varied to control the yield and product distribution of the palladium-catalyzed aminocarbonylation of aromatic bromides in both a silicon microreactor and a packed-bed tubular reactor. Automation of the system set points and product sampling enabled facile and repeatable reaction analysis with minimal operator supervision. It was observed that the reaction was divided into two temperature regimes. An automated system was used to screen steady-state conditions for offline analysis by gas chromatography to fit a reaction rate model. Additionally, a transient temperature ramp method utilizing online infrared analysis was used, leading to more rapid determination of the reaction activation energy of the lower temperature regimes. The entire reaction spanning both regimes was modeled in good agreement with the experimental data.